帝国主義下のマッドサイエンス――蘭郁二郎「宇宙爆撃」試論―― Mad-Science under Imperialism: Ran Ikujirō’s “Space Bombing” - Suzuki, Yūsaku (Silva Iaponicarum, 2024)
This paper discusses the critiques of the imperial world image in Ikujirō Ran’s unpublished work Space Bombing. In this work, the researcher Murao, who works at the Borneo branch of the Institute of Magnetics, studies a “microscopic world” in which microscopic humans live in an atomic structure. He falls into the delusion that there are a minimal world within the atomic structure and a larger world where Earth is considered as a single atom. This paper argues that Murao’s perception was based on the scientific knowledge of the scientist Hantarō Nagaoka. The cosmology reflects the wartime image of the world, and we argue that the larger world implies the Western world, the human world implies Japan, and the minimal world implies the colonial world. Moreover, we suggest that Murao’s mad science indicates that the imperial world's configuration is not an absolute domination vs.no-domination relationship, but merely a relative relationship, and that the clashes between civilizations are able to be interpreted as insane.